Orthostatic intolerance without postural tachycardia: how much dysautonomia? - Parsaik, Ajay K. (2013)
BACKGROUND: Chronic symptoms of orthostatic intolerance occur in postural tachycardia syndrome (POTS) and patients with orthostatic intolerance (OI) without tachycardia. We recently reported that deconditioning is almost universal in both patient groups. In this study, we focussed on the question of how much dysautonomia, besides orthostatic tachycardia, is there in POTS vs. OI, and how the two groups compare in regards to clinical, autonomic, laboratory, and exercise variables. METHODS: We retrospectively studied all patients referred for orthostatic intolerance at Mayo Clinic between January 2006 and June 2011, who underwent standardized autonomic and exercise testing. RESULTS: Eighty-four POTS and 100 OI fulfilled inclusion criteria, 89 % were females. The mean age was 25 and 32 years, respectively. Clinical presentation, autonomic parameters, laboratory findings, and degree of deconditioning were overall similar between the two groups, except for the excessive orthostatic heart rate (HR) rise and mild vasomotor findings observed in POTS but not in OI (slightly larger Valsalva ratio and incomplete blood pressure recovery during Valsalva). Both groups responded poorly to various medications. Severely deconditioned patients were similar to non-deconditioned patients, except for 24 h urine volume (1,555 vs. 2,417 ml), sweat loss on thermoregulatory sweat test (1.5 vs. 0.5 %), and few respiratory parameters during exercise, which are likely clinically insignificant. CONCLUSION: Though similar in clinical presentation, POTS and OI are different entities with greater, albeit still mild, dysautonomia in POTS. The clinical and pathophysiological relevance of minimal dysautonomia in the absence of orthostatic tachycardia as seen in OI remain uncertain.